Conodonts of the genus Lochriea in Ireland and the recognition of the Viséan–Serpukhovian (Carboniferous) boundary. (13th August 2014) - Barham, Milo; Murray, John; Sevastopulo, George D.; Williams, D. Michael
Abstract : Conodonts of the genus Lochriea offer high‐resolution biostratigraphical differentiation of the upper Mississippian (Carboniferous). In particular, L. ziegleri is regarded as the most suitable index taxon for recognition of a revised Viséan–Serpukhovian boundary and selection of a Global Stratotype Section and Point. Mixed carbonate‐siliciclastic Carboniferous sections from western Ireland demonstrate that gradual morphological evolution is expressed within the Lochriea lineage, evidenced by P1 ‐elements with progressively more complex ornament appearing in a pulsed fashion in the Late Viséan. Significant diversification of the Lochriea conodonts occurs below the currently recognized base of the Namurian (identified by ammonoids), with which the basal Serpukhovian has been correlated in the past. The First Appearance Datum (FAD) of L. ziegleri in the Lugasnaghta Section of western Ireland is apparently coincident with the FAD's of other complexly ornamented Lochriea species (e.g. L. cruciformis ) and corresponds with the Irish and British P2a ammonoid biozone and the lower part of the upper Cf6 δ (MFZ15) foraminiferal biozone. The FAD of L. ziegleri in Ireland is closely related to other Lochriea morphotypes with complex ornament, which are difficult to identify to species level using current species definitions. These forms, recorded from the three sections examined (St Brendan's Well, Kilnamona and Lugasnaghta), may partly be explained as abnormal growth histories, evolutionary intermediate forms, etc. In some instances, however, the apparently consistent and novel morphotypes suggest that current Lochriea taxonomy needs to be re‐examined. Furthermore, given the close association of the morphologies with asymmetric complex ornament and L. ziegleri, these taxa may hold significance as biostratigraphical tools in their own right.